Global value chains : measurement and application - Su, Qingyi, 1984- (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"This book aims to help readers understand the status of the division of labour in global value chains, its impact on traditional research topics, and to familiarise readers with the application of input-output methods in GVC research. The book features a combination of practices in China and offers international comparisons. Chapters 1 to 4 discuss the measurement of global value chains, specifically the measurement of the location of production, the status of the division of labour and the risk of the GVC, as well as the GVC and the domestic value chain (DVC). Chapters 5 to 8 focus on the applications of GVCs in the study of traditional topics such as the structure of international trade, the factor content of foreign trade, the real effective exchange rate and environmental pollution. This book will be a great read to students and scholars of statistics, economics, international trade, and those interested in China's economy in general"--
Keywords: International trade; International division of labor; Business logistics; BUSINESS & ECONOMICS / Commerce; BUSINESS & ECONOMICS / Development / Economic Development